2018
DOI: 10.4103/jlp.jlp_97_17
|View full text |Cite
|
Sign up to set email alerts
|

Internal quality control of blood products: An experience from a tertiary care hospital blood bank from Southern Pakistan

Abstract: INTRODUCTION:Internal quality control (IQC) is the backbone of quality assurance program. In blood banking, the quality control of blood products ensures the timely availability of a blood component of high quality with maximum efficacy and minimal risk to potential recipients. The main objective of this study is to analyze the IQC of blood products as an indicator of our blood bank performance.METHODS:An observational cross-sectional study was conducted at the blood bank of Liaquat National Hospital and Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
1
10
0
5
Order By: Relevance
“…Two studies from human transfusion centres have addressed this fact: the first, published in 1992 and performed in six different transfusion centres, reported that only 40.9% of FFP units had <70% factor VIII, while the second study, published in 2018, reported that >70% of factor VIII activity was observed in 95% of the FFP units. 17,18 Both studies were performed in different countries, but the authors hypothesised that this could also reflect storage and management improvements over time, as 16 years separate both studies. In the future, the same improvements may be observed in feline plasma blood banking as more knowledge is gathered, allowing the improvement of storage protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from human transfusion centres have addressed this fact: the first, published in 1992 and performed in six different transfusion centres, reported that only 40.9% of FFP units had <70% factor VIII, while the second study, published in 2018, reported that >70% of factor VIII activity was observed in 95% of the FFP units. 17,18 Both studies were performed in different countries, but the authors hypothesised that this could also reflect storage and management improvements over time, as 16 years separate both studies. In the future, the same improvements may be observed in feline plasma blood banking as more knowledge is gathered, allowing the improvement of storage protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Les moyennes de l'hématocrite étaient 62,11±10,19 et 60,27±10,77 respectivement pour les CGRUA et CGRUE. Au Pakistan, Sultan S et al ont retrouvé un résultat similaire soit 69.5±7.24 sur 400 CGR contrôlés [3]. Pour l'hématocrite, 43,13% (n=64) des CGRUA étaient conformes.…”
Section: Discussionunclassified
“…Dans la thérapeutique transfusionnelle, les concentrés de globules rouges (CGR) sont utilisés essentiellement dans les anémies symptomatiques avec pour but d'améliorer le taux d'hémoglobine (Hb) du patient [1, 2]. Pour assurer l'efficacité de la transfusion, il faut utiliser le bon produit chez le bon patient au bon endroit et au bon moment [3, 4]. Depuis l'année 2003 que le CNTS produit et distribue différents produits sanguins labiles, une seule étude de contrôle qualité de ces produits fut réalisée en 2006 [5].…”
Section: Introductionunclassified
“…There have been sporadic reports of resistance to azithromycin [47,48], and this is of concern given its widespread use in the outpatient management of typhoid fever and other systemic infections. Azithromycin treatment produces higher intracellular concentrations than serum levels of the antibiotic and it is thus difficult to interpret laboratory azithromycin sensitivity for S. Typhi [49].…”
Section: Azithromycinmentioning
confidence: 99%